1996
DOI: 10.1108/00400919610112079
|View full text |Cite
|
Sign up to set email alerts
|

NVQs in small businesses: factors influencing adoption

Abstract: Reports the findings and conclusions of a study of five small businesses in the hotel and catering sector which had adopted national vocational qualifications (NVQs). Using an open system model, a comparative case study design and a range of data sources and methods of data collection within each organization, traces the preconditions, processes, outcomes and problems/issues associated with NVQ adoption and implementation. In a small business context, this is shown more likely to be successful where there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The importance of understanding how large and varied the small business sector can be has been emphasised by earlier commentators who stressed the need for researchers to differentiate between groups within it (see Table I). Penrose (1959), and later Hawkins and Winter (1996) and Hawkins et al (1995) pointed out that because of its size and diversity, research results cannot be easily generalised across all small …”
Section: Small Firm Size and Sector Diversitymentioning
confidence: 96%
See 1 more Smart Citation
“…The importance of understanding how large and varied the small business sector can be has been emphasised by earlier commentators who stressed the need for researchers to differentiate between groups within it (see Table I). Penrose (1959), and later Hawkins and Winter (1996) and Hawkins et al (1995) pointed out that because of its size and diversity, research results cannot be easily generalised across all small …”
Section: Small Firm Size and Sector Diversitymentioning
confidence: 96%
“…Here``very small'' SMEs had less than 20 employees,``small'' SMEs were between 20-50 employees while``large'' SMEs encompassed 21-499 employees Parker et al (1995) Distinguished between SSEs (small scale enterprises with 6 to 49 workers) and MSEs (micro-enterprises with 1 to 5 workers) in African study Neitzert (1996) Neitzert (1996 focused on those with five or fewer workers (African study) Hales et al (1996) In UK specific sector study of hospitality-based companies, 50 was suggested as the upper limit Casson (1996) Cautioned that equating companies by size without looking at sector may also lead to difficulties given differences found in management style between companies of similar size but within different business sectors Hyland and Matlay (1997) Distinguishing within the size ranges found that 78 per cent were``microenterprises'' i.e. less than ten, within a sample of 1,986 firms OECD, 2000OECD, , 1997OECD, , 1996 Reports focus on``less than 500'' as the measure of a small and medium size company (2000,1997,1996) EU/ESF definition, , 1998European Council, 2000 Definitions of an SME have``less than 250 employees'' as their upper limit across all sectors although 98 percent are micro enterprises, i.e.…”
Section: Burns and Myers (1994)mentioning
confidence: 99%
“…1 For a discussion on the experience of NVQ implementation in diverse types of organisations, including retail ones, see Davison et al, 1998;Hales et al, 1999;Matlay and Hyland, 1997;Messenger, 1997. 2 See Mortlock et al (2000 for a review of the level of food hygiene training in the UK food industry, including the small independent retail sector.…”
Section: Notesmentioning
confidence: 99%
“…Small firms are also deterred by negative views of NVQs being top-down, prescriptive and with little evidence that they lead to improvements (Welsh, 1996). However, key determinants of the amount of training in small firms are the link between training and organisational success (Hyland & Matlay, 1997) and the presence of a training culture and infrastructure (Hales et al, 1996). Of more import, perhaps, are the returns derived from particular qualifications.…”
Section: Costs and Returnsmentioning
confidence: 99%